Application of PjBL with brain-based STEAM approach to improve learning achievement of students - Nur Lailatul Badriyah; Anik Anekawati; Lutfiana Fazat Azizah (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2020)
The purpose of this study is to determine differences in student's learning achievement consisting of learning outcomes and science process skills. This research was conducted in a special school for girls and used two experimental classes, namely experimental class-1 and experimental-2 class. The experimental class-1 is the class applied by PjBL with a brain-based STEAM approach, while the experimental class-2 is a class that uses PjBL with the STEAM approach without brain-based. This research is a quasi-experimental study with a nonequivalent pretest-posttest control group design. The data analysis technique used is the T-test. The brain-based learning activities applied in this study are listening to music, drinking water, doing a brain gym, working on crossword puzzles, and group determination based on the dominance of students' brains. The results showed that the average value of the N-Gain score of student learning outcomes in the experimental class-1 was 80,72. Student learning outcomes experimental class-2 is 73,12. In science process skills, the experimental class-1 students had an average N-Gain score of 72,50, while the experimental-2 class was 60,88. The conclusion is the experimental class 1 students have higher learning achievement than students in the experimental class 2.